(untitled) (International journal of artificial intelligence, 2026)
Introduction. The intensive development of industry, urbanization, and the growth of technogenic load have led to a significant increase in the concentration of heavy metal ions in natural and wastewater. These pollutants are characterized by high chemical resistance, the ability to accumulate bio, and a pronounced toxic effect on biological systems, which determines their particular ecological and sanitary hazard [1,2]. Unlike organic compounds, heavy metals do not undergo biodegradation and can circulate in the environment for a long time, transitioning from one ecosystem to another.